The Implementation of Farm-to-University Program in Historically Black Colleges and Universities: Assessment of Feasibility and Barriers. Issue 6 (2nd November 2022) - Vilme, Helene; Campbell, Santiba D.; Sauls, Derrick L.; Powell, Keith; Lee, Jennifer; Stout, Robyn; Erkanli, Alaattin; Reynolds, Glenn; Story, Mary T.; Matsouaka, Roland A.; Austin, Tomia; Templeton, P. Gizem; et al.
ABSTRACT: Background: Farm-to-University (Farm2U) programs make healthy eating accessible, easier, and the default option. Yet, few published studies have focused on Farm2U implementations in Historically Black Colleges and Universities (HBCUs) in conjunction with measurements of implementation barriers using the consolidated framework for implementation research (CFIR). Purpose: The purpose of this study was to assess the feasibility of delivering a Farm2U program in four HBCUs in North Carolina. Methods: Using a quasi-experimental pre-posttest design, four HBCUs were allocated to either the intervention or the control group. The program was administered over a 4-month period and data were collected at baseline and at post-program implementation. Results: With a target sample size of 128, we successfully recruited 351 participants, retaining 138 at follow-up, for a retention rate of 39%. Twelve CFIR constructs were measured, ten emerged as facilitators and two as mixed barriers/facilitators to program implementation. We observed an increase in local produce purchases and a significant increase in the daily intake of fruits for students. Discussion: This study demonstrated that a Farm2U program is feasible in HBCUs. Translation to Health Education Practice: Certified Health Education Specialists can use the findings to implement Farm2U programs that promote healthy food environments in school settings.